2019
DOI: 10.1109/tcomm.2019.2918454
|View full text |Cite
|
Sign up to set email alerts
|

Space–Time Signal Design for Multilevel Polar Coding in Slow Fading Broadcast Channels

Abstract: Slow fading broadcast channels can model a wide range of applications in wireless networks. Due to delay requirements and the unavailability of the channel state information at the transmitter (CSIT), these channels for many applications are non-ergodic. The appropriate measure for designing signals in non-ergodic channels is the outage probability. In this paper, we provide a method to optimize STBCs based on the outage probability at moderate SNRs.Multilevel polar coded-modulation is a new class of coded-mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…We have thus shown that for every λ 1 , λ 2 > 0 and sufficietnly large n, there exists a (2 nR , n, λ 1 , λ 2 ) code. The proof follows by taking the limits n → ∞, and b → 0, hence the rate tends to 1 4 by (26).…”
Section: Codebook Constructionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have thus shown that for every λ 1 , λ 2 > 0 and sufficietnly large n, there exists a (2 nR , n, λ 1 , λ 2 ) code. The proof follows by taking the limits n → ∞, and b → 0, hence the rate tends to 1 4 by (26).…”
Section: Codebook Constructionmentioning
confidence: 99%
“…In some applications, the receiver may acquire channel side information (CSI) by instantaneous estimation of the channel parameters [19]- [21]. On the other hand, in the slow fading regime, the latency is short compared to the coherence time [14], and the behaviour is that of a compound channel [22]- [26].…”
Section: Introductionmentioning
confidence: 99%